PENGEMBANGAN E-COMIC BERBASIS PROBLEM BASED LEARNING (PBL) MATERI SISTEM EKSKRESI MANUSIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Hia, Kristina Nastina (TUNAS : Jurnal Pendidikan Biologi, 2024)
This research was conducted because E-comic learning media based on Problem Based Learning material on the human excretory system was not yet available at Lolowau 2 State Junior High School and student learning outcomes did not meet the Minimum Completeness Criteria. The research applied is development research (Development Research) with the four D model. The results of the research obtained an average validity test score of 89.52%, practicality test by teachers 3.50 while students 3.57 and an average effectiveness test score 90.14 so it can be concluded that E-comic learning media can be applied in the learning process of human excretory system material in class Vlll.